On uniform in time error estimates for investigation of nonlinear difference schemes - Čiegis, Raimondas; Štikoniene, Olga (Mathematical Modelling and Analysis, 1997)
“On uniform in time error estimates for investigation of nonlinear difference schemes”Mathematical Modelling Analysis, 2(1), p. 48-60.First Published Online: 14 Oct 2010